Effect of poly [styrene‐b‐(ethylene‐co‐butylene)‐b‐styrene] (SEBS) and maleic anhydride‐grafted SEBS triblock copolymers in immiscible blends of (polyamide‐6)/polycarbonate: Morphology‐mechanical properties relationships. Issue 4 (19th July 2014) - Yazdani Sarvestani, M.R.; Arefazar, A.; Moini Jazani, O.; Saeb, M.R.
Abstract : The effects of using maleated poly[styrene‐b‐(ethylene‐ co ‐butylene)‐b‐styrene] triblock copolymer ( SEBS‐g‐MAH ) and unmodified SEBS ( unSEBS ) on the phase morphology and mechanical properties of immiscible polymer blends of polyamide‐6 (PA‐6) and polycarbonate (PC) are investigated. Different binary, ternary, and quaternary blends were prepared by using a Brabender® co‐rotating twin‐screw extruder. The weight ratio of unSEBS to SEBS‐g‐MAH was changed to probe the phase morphology and mechanical properties. The results revealed that the mechanical properties of (PA‐6)/PC/( unSEBS / SEBS‐g‐MAH ) blends were considerably governed by the unSEBS to SEBS‐g‐MAH weight ratio. Morphological investigation based on the spreading coefficient concept confirmed the results of scanning electron microscopy, indicating encapsulation of unSEBS domains around the PC core‐forming component in the presence of reactive SEBS‐g‐MAH precursor. Moreover, larger unSEBS ‐PC composite droplets appeared throughout PA‐6 matrix upon increasing the ratio of unSEBS to SEBS‐g‐MAH, until reaching a maximum value. In the case of the (PA‐6)/PC blend compatibilized with a 50/50 combination of unSEBS and SEBS‐g‐MAH, the highest mechanical properties, i.e., tensile strength, impact resistance, and strain at break, were achieved owing to compatibilizing effect of virgin and maleated SEBS constituents. J. VINYL ADDIT. TECHNOL., 21:245–252, 2015. © 2014 Society of Plastics Engineers